Implementation of Traditional Games in Ethnoscience Learning - Sri Supiyati; M. Khairul Wazni; Dadang Warta Chandra Wira Kusuma; Agus Muliadi (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to explore the perceptions of preservice teachers on the implementation of traditional Sasak tribe games in ethnoscience learning. This exploratory research was conducted at the Mandalika University of Education with a subject pool of 294 preservice teacher students. The research utilized a validated closed questionnaire instrument with responses gathered using a Likert scale. The data from this study were analyzed using quantitative descriptive statistics. The results of this study are (1) preservice teachers’ perceptions of the implementation of traditional Sasak games in ethnoscience learning in each item of the statement, namely item 1 scored 3.30, categorized as Very High; item 2 scored 3.22, categorized as Tall; item 3 scored 2.88, also categorized as Tall; item 4 scored 3.41, categorized as Very High; item 5 scored 3.19, categorized as Very High; item 6 scored 3.28, categorized as Very High; item 7 scored 3.13, categorized as Tall; item 8 scored 3.38, categorized as Very High; item 9 scored 3.37, categorized as Very High; and item 10 scored 3.47, categorized as Very High; (2) preservice teachers hold highly favorable perceptions regarding the implementation of traditional Sasak games in ethnoscience learning, proven by the average score of 3.26, categorized as Very High.